NILAI NORMAL PEMERIKSAAN NEUROPSIKOLOGI CERAD DI JAKARTA - Abdul Wahid Indrajaya, Silvia Francina Lumempouw, Yetty Ramli, Joedo Prihartono (NEURONA, 2013)
INTRODUCTION CERAD NEUROPSYCHOLOGY EXAMINATION IS AN INSTRUMENT THAT CAN BE USED TO DETECT COGNITIVE IMPAIRMENT ESPECIALLY DETERMINING THE TYPE OF DEMENTIA TO DATE NORMATIVE VALUE OF THAT EXAMINATION HAS NOT BEEN KNOWN